Characterising the adipose-inflammatory microenvironment in male breast cancer. Issue 7 (July 2018) - Lees, Tom; Cullinane, Angharad; Condon, Alexandra; Shabaan, Abeer M; Humphries, Matthew P; Speirs, Valerie
Abstract : Male breast cancer (MBC) incidence seems to parallel global increases in obesity. The stromal microenvironment contributes to carcinogenesis; yet, the role of adipocytes in this is understudied in MBC. We identified four cohorts of male breast tissues diagnosed when obesity was rare (archival cohort) and more common (contemporary cohort). We examined the microenvironment of archival and contemporary cohorts of MBC, diagnosed 1940–1970 and 1998–2006, respectively, with two cohorts of, archival and contemporary gynaecomastia, diagnosed 1940–1979 and 1996–2011, respectively, serving as controls. We quantified adipocytes, crown-like structures (CLS) and the presence of CD8, α smooth muscle actin (αSMA) and CD68+ macrophages in both cohorts, and determined how these affected survival, in the contemporary MBC cohort. In both MBC cohorts, mean adipocyte diameter was larger in the distant stroma compared with stroma close to the invading tumour (92.2 µm vs 66.7 µm). This was not seen in gynaecomastia. CLS were more frequent in both MBC cohorts than gynaecomastia (44/55 (80%) vs 11/18 (61%), P < 0.001). No relationship was found between CLS number and adipocyte size, although there were greater numbers of CLS in contemporary MBC > archival MBC > gynaecomastia. CD8 and CD68 expression in the stroma was significantly associated with reduced survival, with no effects seen with αSMA. Changes in the adipose-inflammatory microenvironment may be a contributing factor to the increase seen in MBC diagnosis.